2016
DOI: 10.1371/journal.pone.0158166
|View full text |Cite
|
Sign up to set email alerts
|

Control of Insulin Secretion by Production of Reactive Oxygen Species: Study Performed in Pancreatic Islets from Fed and 48-Hour Fasted Wistar Rats

Abstract: Mitochondria and NADPH oxidase are important sources of reactive oxygen species in particular the superoxide radical (ROS) in pancreatic islets. These molecules derived from molecular oxygen are involved in pancreatic β-cells signaling and control of insulin secretion. We examined the involvement of ROS produced through NADPH oxidase in the leucine- and/or glucose-induced insulin secretion by pancreatic islets from fed or 48-hour fasted rats. Glucose-stimulated insulin secretion (GSIS) in isolated islets was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 54 publications
3
32
0
1
Order By: Relevance
“…Various physiological parameters are known to be altered in the endocrine pancreas during acute fasting, including insulin syntheses, glucose-stimulated insulin secretion (GSIS), glucose utilization, pancreatic islet metabolism, and pancreatic β-cell sensitivity to glucose [44][45][46][47][48][49][50]. Our group showed that a 48-hour acute fast increases net reactive oxygen species (ROS) production in isolated pancreatic islets and alters GSIS [51]. Thus, in the present study, we sought to evaluate the effects of 12 weeks of IF on glucose homeostasis and pancreatic islets isolated from rats.…”
Section: Introductionmentioning
confidence: 99%
“…Various physiological parameters are known to be altered in the endocrine pancreas during acute fasting, including insulin syntheses, glucose-stimulated insulin secretion (GSIS), glucose utilization, pancreatic islet metabolism, and pancreatic β-cell sensitivity to glucose [44][45][46][47][48][49][50]. Our group showed that a 48-hour acute fast increases net reactive oxygen species (ROS) production in isolated pancreatic islets and alters GSIS [51]. Thus, in the present study, we sought to evaluate the effects of 12 weeks of IF on glucose homeostasis and pancreatic islets isolated from rats.…”
Section: Introductionmentioning
confidence: 99%
“…This high ROS content was associated with an increased interaction of the cytosolic NOX subunit p47 phox to the membrane-bound gp91 phox , a key step in the activation of the oxidase system, and subsequent ROS generation. Islets treated with VAS2870 caused a reduction in ROS content at 2.8 mM glucose, demonstrating that NOX possesses a high activity at low glucose levels (Munhoz et al 2016). Previous works have also demonstrated that melatonin can directly regulate ROS generation and modulate pro-oxidant enzymes expression, such as the NADPH oxidase (Zhou et al 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Hydrogen peroxide is naturally produced and degraded by enzymes inside and outside cells, where it serves as a signaling molecule in a variety of biological processes from cell death and cell proliferation to protein secretion and gene expression . It has the property to dismutate to generate oxygen or radicals and can potentially be cytotoxic due to its high oxidizing potential .…”
Section: Hydrogen Peroxide (H2o2)mentioning
confidence: 99%